Hic situs est: occupational identity of Roman jewelers - Kret, Patricia (Student Undergraduate Research E-journal!, 2016)
In their grave inscriptions craftsmen – or their living relatives – mentioned their occupation and other aspects of their identity: the location of their workshop, supporting their former slaves as a patronus and being a member of/having a function in a collegium. However, they did not mention their skills. Craftsmen chose to show how successful they were, because they had to earn enough money to be able to do all this. This way they created an identity of individual financial success that fits the elite ideal of economic identity. This created identity gave the craftsmen social status.